The microstructural effect of chemically vapor infiltrated SiC whiskered thin film on the green body of SiC/C composites - Lee, YJ; Hwang, SM; Choi, DJ; Park, SH; Kim, HD (ELSEVIER SCIENCE SA, 2002)
SiC films have been grown by a chemical vapor infiltration and deposition method. Different microstructures, so-called 'whisker-type' SiC films, have been fabricated, and the deposition and infiltration conditions of whisker growth have been studied. By connecting the SiC/C particles of the green body, fractural strength has been increased and, subsequently, the open pore structure of the body has been modified by an infiltrated whiskering process without a canning effect. Without using a metallic catalyst, silicon carbide whiskers have been obtained at an input gas ratio (H-2/MTS) above 20, and at temperatures below 1200 degreesC. The microstructure and composition of the whiskered SiC have been investigated by means of SEM and XPS. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: SILICON-CARBIDE WHISKERS; RICE HULLS; DEPOSITION; GROWTH